Performance and organizational stressors in the junior-to-senior transition in football - Andreas Rye; Daniel Ransom; Martin Littlewood; Stig Arve Sæther (Bern Open Publishing, 2022)
Both elite sport and the road to elite sport performance could be described as stressful. The junior-to-senior transition has proven to be difficult for many talented football players because of the often non-normative nature of the transition. The aim of the current study was to investigate junior football players perception of performance and organizational stressors in the junior-to-transition. Ten players (5 junior-elite, 5 junior non-elite) were inter-viewed, and the data were thematically content analysed. The highlighted performance stressors were pressure to perform, and preparations related to performance issues. Among organizational stressors were increased level of performance and uncertainty of outcome related to environmental issues. Difficulties related to dual career and prioritizing football before friends were related to personal issues, lack of coaching were leadership issues, and maladaptive communication were related to team issues. The overall findings in one of few studies on junior players in football indicate access to performance arenas, while lack a social affiliation to the senior team players and lack of feedback from the senior team coaches and lack a mastery arena including social support. The results from this would highlight the importance of adjusting stressors for players in the junior-to-senior transition in football.